Web-Based Local Product Sales Information System in Bajo Village, Tilamuta District, Boalemo Regency - Rahmat Thaib; Hamsir Saleh; Nurain C Iding (Formosa Journal of Sustainable Research, 2023)
Web-Based Local Product Sales Information System in Bajo Village, Tilamuta District, Boalemo Regency was designed using the waterfall method. Waterfall is the earliest Software Development Life cycle approach used for software development. Bajo Village is a village located on the coast which is located in Boalemo Regency, Gorontalo Province or what is commonly referred to as the Bajo tribe. The majority of the Bajo villagers make a living as fishermen. the Bajo village community began to develop their creativity by utilizing marine products such as sea shells and seaweed which were used as local products. Sales of local products are still carried out in the traditional way by visiting people's homes. This web-based local product sales information system can facilitate data processing, increase sales and facilitate product marketing and promotion to outsiders